Spectators of Suffering: Witnessing Victims of Jungle Justices on Social Media - Nwakpu, Ekwutosi Sanita; Ogbodo, Jude Nwakpoke; Nwakpu, Iruka Wilfred; Oyeleke, Adeola Sidikat (Mediterranean Journal of Social Sciences, 2020)
With the availability of the media, no one will deny both proximal and distance happenings across the globe especially when it is about suffering of others. The visibilities of these sufferings of others are much triggered with the emergence of new media. People of different socio-cultural and demographic background have adopted social media as means of letting the world know the happenings around them. In Nigeria through the medium, people have become witnesses to the suffering of victims of jungle justice as their images are constantly displayed on daily basis. Existing studies on audience reaction to suffering of others through mediated images shows that audience response to such images are dependent on their gender, socioeconomic, political and religious background, and some arguing that they have become numb and no longer care about suffering of others. Though these may be true, it cannot be generated to Nigeria audiences as a lot of factors determine how audience responded to mediated images. Little or no study of Nigeria background verified how Nigerians respond to suffering of others especially on the victims of disaster and attacks such as jungle justice. It is against these backdrops that this study through survey (focus group interview) determines Nigerian respond to images of victims of jungle justices in Nigeria. The finding reveals that Nigerians are not numbs when faced with such images and reaction is that of pity and ‘it could have been me’ with the sense of responsibility as to help avert the suffering.